2014
DOI: 10.1021/la502595t
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hydrophobin on Different Self-Assembled Monolayers: The Role of the Hydrophobic Dipole and the Electric Dipole

Abstract: In this work, the adsorptions of hydrophobin (HFBI) on four different self-assembled monolayers (SAMs) (i.e., CH3-SAM, OH-SAM, COOH-SAM, and NH2-SAM) were investigated by parallel tempering Monte Carlo and molecular dynamics simulations. Simulation results indicate that the orientation of HFBI adsorbed on neutral surfaces is dominated by a hydrophobic dipole. HFBI adsorbs on the hydrophobic CH3-SAM through its hydrophobic patch and adopts a nearly vertical hydrophobic dipole relative to the surface, while it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 60 publications
5
99
0
Order By: Relevance
“…An exception was HFB7, where preincubation failed to show any stimulation of hydrolysis by the cutinase, and it is possible that HFB7 indeed does not bind to PET. A refined explanation for the stimulatory effect of hydrophobins on PET hydrolysis by cutinase may be offered by the recent data of Peng et al (30), who showed that the T. reesei hydrophobin HFB1 (class II) adsorbs to a hydrophobic surface through its hydrophobic patch and adopts a nearly vertical hydrophobic dipole relative to the surface. If such an orientation would also occur on PET, the hydrophobins could physically interact with the cutinases, while leaving enough surface of the polymer for cutinase binding.…”
Section: Discussionmentioning
confidence: 99%
“…An exception was HFB7, where preincubation failed to show any stimulation of hydrolysis by the cutinase, and it is possible that HFB7 indeed does not bind to PET. A refined explanation for the stimulatory effect of hydrophobins on PET hydrolysis by cutinase may be offered by the recent data of Peng et al (30), who showed that the T. reesei hydrophobin HFB1 (class II) adsorbs to a hydrophobic surface through its hydrophobic patch and adopts a nearly vertical hydrophobic dipole relative to the surface. If such an orientation would also occur on PET, the hydrophobins could physically interact with the cutinases, while leaving enough surface of the polymer for cutinase binding.…”
Section: Discussionmentioning
confidence: 99%
“…43,51 For PTMC simulations, N replicas were parallel simulated, each in the canonical ensemble with a different temperature T. Details were the same as interpreted in our previous studies. [43][44][45]50,52 The MC simulation in each replica was carried out in a box of 150 Â 150 Â 150 Å 3 . The protein was initially put 75 Å above the model surface with a random orientation, and then the protein was translated and rotated around its centre of mass during simulations.…”
Section: Ptmc Simulation Detailsmentioning
confidence: 99%
“…Peng et al 50 adopted the hydrophobic dipole to study hydrophobin adsorption on different SAMs and implied that the hydrophobic dipole may be applied to predict the probable orientations of a protein adsorbed on a hydrophobic surface. Lipase adsorption on surfaces with varying polarity has been explored experimentally and theoretically.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Due to their unique properties, hydrophobins have become attractive for use in several types of biotechnical applications. These include stabilization of colloidal dispersions, reverse the wettability of surfaces, dispersion of insoluble drug compounds, production of stable foams, and protein immobilization [8, 1013]. Hydrophobins are very soluble in water up to 100 mg/mL and display unusual detergent-like behaviour in solution as they form different kinds of oligomers, depending on the conditions and on the hydrophobin type [9, 14, 15].…”
Section: Introductionmentioning
confidence: 99%